MY PATH TO LAW AND MODERNIZATION AT YALE, 1968-70: A MEMOIR OF RADICALIZATION - Kennedy, Duncan (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2021)
In his paper for this collection on the history of the L&M program at the Yale Law School and in several other papers, David Trubek “affectionately” attributes a role to me, as a sort of angel of destruction or a fox in the chicken coop, a “nightmare.” This is exaggerated! I did, however, play a part in supporting the emergence from the program of legal academic projects--the Law and Society Association, the field of law and development and critical legal studies--that rejected some of the meliorist liberal Cold War assumptions of the program’s initial formulation. That involved intense academic discussions among and between students and teachers who understood ourselves to share a deep intellectual, political and often affective bond. It was a moment of radicalization. It was simultaneously about the role of the US in the world, Vietnam and the imperialist project in the background, and equally about the dramatic crisis in race relations as black opposition to white supremacy turned to various forms of violence. Although we were all pre-boomers, assistant profs and graduate students, it was no less intense than what was happening on college campuses. For all that, it is true as Dave affirms that I was vocally critical of a basic premises of the program: that making the legal systems of “underdeveloped countries” work better according to the model of the US legal system would be in the interest of those countries because it would promote economic development. My skepticism extended to the foundational idea that “modernization” itself, understood as economic development based on industrialization, with accompanying societal and institutional changes, was a benign as well as inevitable process (as long as it did not devolve into communism).